Anlotinib combined with tislelizumab in the treatment of primary small cell neuroendocrine carcinoma of the prostate: a case report and literature review - Fei, Xin; Zheng, Zhong; Zhao, Zhen-ya; Ren, Da-wei; Wang, Su-ying; Ye, Shi-jie; Liang, Lin-chun; Li, Da; Jia, Xiao-long; Ma, Qi (Frontiers in Immunology, 2024)
Primary small cell neuroendocrine carcinoma of the prostate is extremely rare, highly aggressive, and has a very poor prognosis, with an overall survival typically not exceeding one year. Standard treatment is generally based on the regimen for small cell lung cancer (SCLC), with guidelines recommending etoposide combined with cisplatin (EP regimen) as the first-line treatment. However, their therapeutic effects are limited. For primary small cell neuroendocrine carcinoma of the prostate that has failed the EP regimen treatment, there is currently a lack of relevant treatment methods. Here, we report a case of small cell neuroendocrine carcinoma of the prostate with multiple metastases, whose disease rapidly progressed despite receiving EP and second-line systemic chemotherapy. The patient was then administered a combination of anlotinib and tislelizumab. After treatment, the patient’s symptoms were controlled, tumor marker levels decreased, and imaging showed significant improvement. The patient had a progression-free survival time of more than 22 months and continued to receive treatment. This is the first report of the use of anlotinib combined with tislelizumab for the treatment of primary small cell neuroendocrine carcinoma of the prostate, providing a new therapeutic option for patients with this disease.